Development of Local Wisdom–Based Digital Educational Games of the Sasak Tribe to Enhance Second-Grade Students’ Reading Skills - Muna Iffat Nabilah; Asrin; Syaiful Musaddat; Burhanuddin; Fahruddin; Paniran (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a digital educational reading game based on the local wisdom of the Sasak tribe to improve the reading skills of second-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research instruments included validation questionnaires for media and material experts, teacher and student response questionnaires, and an early reading skills test. Data were analyzed using descriptive statistical techniques to determine feasibility and practicality percentages, while effectiveness was measured using the Normalized Gain (N-Gain) formula to assess the improvement between pre-test and post-test scores. The results showed that the developed game was highly feasible, with a percentage of 97.8% from two media experts and 95% from two material experts. The game was also categorized as highly practical, with teacher response percentages of 98.6% and student response percentages of 95.7% and 97.8%. Furthermore, the N-Gain analysis indicated that the game was effective in improving students’ early reading skills in two schools, achieving 74.15% (moderately effective) at SDN 1 Buwun Mas and 76.37% (effective) at SDN 4 Buwun Mas. Therefore, the developed digital educational game is considered feasible, practical, and effective for second-grade reading instruction. The findings contribute theoretically to the literature on Game-Based Learning and Place-Based Education and provide practical implications for the design of culturally responsive instructional media.